3) Resolvendo a equação fracionária 5x-2/9-x² + 3/3+x – 1/3-x=0, para x≠-3 e x≠3, obtemos como conjunto solução;
(A) S={4}
(B) S={-4}
(C) S={2}
(D) S={-2}
Soluções para a tarefa
Respondido por
29
vamos lá...
![\frac{5x-2}{9-x^2} + \frac{3}{3+x} - \frac{1}{3-x} =0 \\ \\ \frac{5x-2}{(3+x)(3-x)} + \frac{3}{3+x} - \frac{1}{3-x} =0 \\ \\ mmc=(3+x)(3-x) \\ \\ 5x-2+3(3-x)-1(3+x)=0 \\ \\ 5x-2+9-3x-3-x=0 \\ \\ 5x-4x+9-5=0 \\ \\ x+4=0 \\ \\ x=-4 \\ \\ S=\{-4\}~~~~letra~~B \frac{5x-2}{9-x^2} + \frac{3}{3+x} - \frac{1}{3-x} =0 \\ \\ \frac{5x-2}{(3+x)(3-x)} + \frac{3}{3+x} - \frac{1}{3-x} =0 \\ \\ mmc=(3+x)(3-x) \\ \\ 5x-2+3(3-x)-1(3+x)=0 \\ \\ 5x-2+9-3x-3-x=0 \\ \\ 5x-4x+9-5=0 \\ \\ x+4=0 \\ \\ x=-4 \\ \\ S=\{-4\}~~~~letra~~B](https://tex.z-dn.net/?f=+%5Cfrac%7B5x-2%7D%7B9-x%5E2%7D+%2B+%5Cfrac%7B3%7D%7B3%2Bx%7D+-+%5Cfrac%7B1%7D%7B3-x%7D+%3D0+%5C%5C++%5C%5C++%5Cfrac%7B5x-2%7D%7B%283%2Bx%29%283-x%29%7D+%2B+%5Cfrac%7B3%7D%7B3%2Bx%7D+-+%5Cfrac%7B1%7D%7B3-x%7D+%3D0+%5C%5C++%5C%5C+mmc%3D%283%2Bx%29%283-x%29+%5C%5C++%5C%5C+5x-2%2B3%283-x%29-1%283%2Bx%29%3D0+%5C%5C++%5C%5C+5x-2%2B9-3x-3-x%3D0+%5C%5C++%5C%5C+5x-4x%2B9-5%3D0+%5C%5C++%5C%5C+x%2B4%3D0+%5C%5C++%5C%5C+x%3D-4+%5C%5C++%5C%5C+S%3D%5C%7B-4%5C%7D%7E%7E%7E%7Eletra%7E%7EB)
Perguntas interessantes
Matemática,
11 meses atrás
Inglês,
11 meses atrás
Biologia,
11 meses atrás
Saúde,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás